Label-free monitoring of DNA methyltransferase activity based on terminal deoxynucleotidyl transferase using a thioflavin T probe. Issue 2 (April 2016) - Ma, Changbei; Liu, Haisheng; Li, Wei; Chen, Hanchun; Jin, Shunxin; Wang, Jing; Wang, Jun
Abstract: We have developed a new methodology for fluorescence turn-on detection of DNA methyltransferase (MTase) activity based on terminal deoxynucleotidyl transferase (TdT) using a thioflavin T probe. This method is highly selective and sensitive. The fluorescence intensity was direct proportion to Dam MTase concentration in the range from 0.1 to 8.0 U/mL with a detection limit of 0.1 U/mL. And because no labeling with a fluorophore–quencher pair was required, it is simple and low cost. We envision that our novel fluorescent detection method for Dam MTase activity could be applied as a useful tool in biomedical research. Highlights: A novel, label-free fluorescence assay has been developed for the detection of Dam methyltransferase (MTase) activity. This method is highly selective and sensitive with a 0.1 U/mL limit of detection. Because no labeling was required, the method is simple and low cost.